A FOUR YEAR RADIOGRAPHIC REVIEW OF BONE FRACTURES AT THE ABRAKA GENERAL HOSPITAL, DELTA STATE IN NIGERIA. - Ese, Anibor; Excel, Uzum Obinna; Tagbire, Mabiaku (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
This intellectual exercise was intended to evaluate bone fractures seen at the Abraka General Hospital in Delta State, Nigeria. This appraisal is a four-year retrospective inquiry which encompassed 244 patients (121 males and 123 females) cared for at the General Hospital in Abraka from January 1st 2017 to December 31st 2020. Ethical accord was gained from the Research/Ethical Board of Anatomy Department, Delta State University, Abraka. Data were copied from the register in the radiology unit and patients’ data such as age, gender, bones fractured and etiology of fracture were noted. Analysis of statistics entailed the use of chi-square test for valuing association between variables. The females (50.4%) were more than the males (49.6%). The femur was frequently fractured (25.0%), and was closely followed by the radius (21.7%). Those persons within the age set of 21-30years (27.0%) were mostly affected, as well as those aged 31- 40years (25.0%). Trauma (38.9%) was the leading cause of fracture which was followed by falls (35.2.9%) with the seldom causative issue being road traffic accident (25.8%). Considerable relationship with a p-value of .001 was observed in a test of association between age and bone fractured as well as causation. In conclusion it was observed that the 21-30years age bracket had a higher tendency to bone fractures and the commonest etiological stimulus is trauma.